Evolución de los modelos de la gestión de innovación (Evolution of innovation administration models) - López Treviño, Oscar Enrique; Blanco Jiménez, Mónica; Guerra Moya, Sergio Armando (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. In this study the tools are analyzed to cause that the PyMEs looks for to be more competitive in the market. The different proposals will appear on the Models of the Innovation Process from already existing and they will focus in the variables that conform these models compatible to analyze each one of the proposals made by the different authors and to integrate a new proposal of variables as a hypothesis that integrates a Model that allows the Pymes of Nuevo Leon to be innovating.